Outcome and Determining Characteristics of ICU Patients with Acute Kidney Injury in a Low-Income Country, a Multicenter Experience - Ballah Abubakar; Mohammed Jika; Njidda Gyadale Abdulhamid; Yahaya Halima Bidemi; Rosemary Nwokorie Mabong; Naziru Ibrahim; Baffah Adamu Yusuf; Maina Hassan Ali; Galadima Hajara; Mohammed Abdullahi Maryam; Andibanbang Franklin; Abdullahi Adam Ibrahim (The Journal of Critical Care Medicine)
Acute kidney injury (AKI) is a disease that affects millions of people globally making it a major public health concern. It is defined as an abrupt decrease in kidney function that occurs within ours affecting both the structure and functionality of the kidneys.